Kritiske refleksioner: I seng med Madonna - de Duve, Thierry; Gregersen, Annette; Lund Pedersen, Jacob (Peripeti, 2024)
In these very personal reflections on his own work as an art critic, Thierry de Duve describes the interaction between theory, involvement and intuition in his meeting with the work of art.